Development of the Belarusian province: a sociological aspect - Sakovich, Anzhela Yu. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The structure of the Belarusian province has been developed. The prospects of its development are considered. It is established that in order to provide the agro-industrial complex with educated, qualified personnel, it is necessary to use the labour resources of not only villages, agro-towns, urban-type settlements, but also small provincial cities. The scheme of transport communication of agricultural enterprises and settlements is presented. The sociological study the social adaptation of young professionals sent to work in the agro-towns of the Myadel district (2019) has revealed the features of housing provision for young people in rural areas. The author proposes practical recommendations for staying of young cadres in rural areas. The heterogeneity of the Belarusian province has been established. It demands the adoption of measures aimed at the development of specific regions, taking into account their natural, geographical, cultural, social, economic, demographic characteristics.